INOVASI PEMBERDAYAAN PAUDQU DARUSSOLIHIN: MEMBANGUN PEMBELAJARAN AL-QURAN INTERAKTIF, MEMPERKENALKAN BAHASA ARAB DAN MENINGKATKAN LITERASI PERBANKAN SYARIAH - Rohwiyono, Anang; Rof’illah, Abid; Syapi’i, Ahmad Abdullah; Anggraeni, Arifah Oktavia; Agustin, Eka Sonya; Azis, Hani Febrian; Magfiroh, Isni Daimatul; Putri, Mualifah Macica; Hasan, Muhamad Fikri; Tihona, Syifa Mawardah; Alrahmado, Vito; Haryadi, Virginia Indriani (LPPM Institut Pendidikan Nusantara Global, 2024)
Social Work Lecture (KKS) is an activity that involves students to be able to participate directly in community activities. After getting lecture material in the form of theory, this KKS is a form of real community service to apply the knowledge gained during lectures. This activity was carried out by FAI UHAMKA students class of 2020. The target of this service is children and the surrounding community in PaudQU Darussolihin. PaudQU Darussolihin, as an institution that has a vision and mission to improve the understanding of Islam for children and the community, especially in reading the Qur'an, is considered a strategic partner to achieve this goal. Students realize that there are a number of challenges faced by the community, especially related to understanding the Quran, Arabic language skills, and Islamic banking literacy. Therefore, students of the Faculty of Islamic Religion, Prof. Dr. Hamka University plan a PSC Program that will focus on innovation in empowering. Through this program, it is expected to build an interactive Quran learning system, utilizing technology to increase the attractiveness and effectiveness of learning. In addition, this activity will also introduce Arabic more thoroughly, from basic to advanced, so that children and our society The surrounding community can understand and apply the language in everyday life. No less important, this program will also provide a deep understanding of Islamic banking literacy, in the form of seminars, and provide practical skills in managing Islamic finances.